Trimethylamine borane: a new single-source precursor for monolayer h-BN single crystals and h-BCN thin films - Tay, Roland Yingjie (2018)
Due to their exceptional chemical and thermal stabilities as well as electrically insulating property, atomically thin hexagonal boron nitride (h-BN) films have been identified as a promising class of dielectric substrate and encapsulation material for high-performance two-dimensional (2D) heterostructure devices. Herein, we report a facile chemical vapor deposition synthesis of large-area atomically thin h-BN including monolayer single crystals and C-doped h-BN (h-BCN) films utilizing a relatively low-cost, commercially available trimethylamine borane (TMAB) as a single-source precursor. Importantly, pristine 2D h-BN films with a wide band gap of ∼6.1 eV can be achieved by limiting the sublimation temperature of TMAB at 40 °C, while C dopants are introduced to the h-BN films when the sublimation temperature is further increased. The h-BCN thin films displayed band gap narrowing effects as identified by an additional shoulder at 205 nm observed in their absorbance spectra. Presence of N–C bonds in the h-BCN structures with a doping concentration of ∼2 to 5% is confirmed by X-ray photoelectron spectroscopy. The inclusion of low C doping in the h-BN films is expected to result in constructive enhancement to its mechanical properties without significant alteration to its electrically insulating nature. This study provides new insights into the design and fabrication of large-area atomically thin h-BN/h-BCN films toward practical applications and suggests that the range of precursors can be potentially extended to other anime borane complexes as well.